Discrimination against Working Women and Its Impact on Their Work Performance in District Sahiwal - Shaheen, Sumera; Naz, Madiha; Ali, Babar; Gillani, Syed Muhammad Ahmad; Abbas, Tahir; Ali, Wajid (Journal of Education and Social Studies, 2023)
Workplace gender discrimination comes in many forms: unequal pay, the disparity in promotions, incidents of sexual harassment, and fewer opportunities, which means that an employee is treated differently or less favorably because of their gender identity. Around the world, four-in-ten working women face discrimination on the job because of their gender. This research explored the issue of discrimination against working women at the workplace and its impact on their work performance in District Sahiwal, Punjab, Pakistan. The quantitative data were collected through a cross-sectional survey. A multistage random sampling technique was used for the data collection. A self-designed interview schedule was administered to 200 females of lower, middle, and higher category employees of public and private institutions of District Sahiwal. In the data analysis, both descriptive and inferential statistical techniques were used. Research findings revealed that females were discriminated more than males in the private sector than in the public sector. The results indicated that 63% of women have adverse physical and mental effects due to discrimination at the workplace. In this regard, 60% of women believed that workplace discrimination increased stress and frustration and reduced job satisfaction, commitment, and motivation. The bivariate analysis also shows that gender discrimination decreases satisfaction and commitment and increases stress levels among working women. Therefore, this study suggested that the government should immediately strengthen legal protections against workplace discrimination based on gender.